Urban Environment and Children’s Spaces: A Study on the Impact of Physical Elements on Social and Psychological Interaction in the Public Spaces of Batna - Besma , Boukhetache; Belkacem , Dib (Journal of Ecohumanism, 2025)
This research investigates the impact of urban furnishing elements in public spaces on children’s behavior within the urban environment. The study is grounded in the premise that the urban environment is not solely composed of built structures but also of the voids and open spaces that give the city vitality and social meaning. Public spaces, as integral components of the urban fabric, represent essential venues for social interaction and community engagement. Since the 1980s, urban theorists such as Jane Jacobs, Jan Gehl, and Geoffrey West have emphasized the need to reconsider the design of public spaces to ensure harmony between spatial organization, social behavior, and the quality of urban life. Children are among the social groups most in need of such spaces and the most affected by their design. The quality, diversity, and arrangement of urban furnishing elements—both natural (vegetation, water features) and man-made (benches, shading devices, lighting, signage, and artistic installations)—play a decisive role in shaping children’s psychological, social, and perceptual development. Conversely, poorly designed or inadequately maintained public spaces can have negative behavioral, cultural, and health impacts on children, diminishing their sense of belonging and connection to their urban surroundings. In the Algerian context, despite the legislative efforts—particularly Article 124 of Municipal Law No. 10-11, which assigns municipalities the responsibility for creating and maintaining public and green spaces—many public areas remain poorly equipped and fail to address the needs of children. The study adopts a statistical methodology based on questionnaires distributed to parents accompanying their children in public spaces during weekends and school holidays. The questionnaire aims to assess parents’ perceptions of public spaces, evaluate the adequacy of urban furnishing elements, and identify their influence on children’s behavior and interaction patterns. The research ultimately seeks to highlight the importance of public spaces as essential extensions of private living environments and to propose design strategies that enhance children’s engagement, comfort, and social development in urban contexts.